CORPORATE CRIMINAL LIABILITY REGARDING IUU FISHING FOLLOWING THE JOB CREATION LAW ENACTMENT - Elvany, Ayu Izza (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2020)
This research analyses how is corporate criminal liability regulation in Indonesia regarding IUU Fishing following the enactment of the Job Creation Law. This research uses both statute approach and conceptual approach as the legal research methods to analyse the issued legal problem. Following the enactment of the Job Creation Law on 5th October 2020, some articles of Law No. 45 of 2009 amending law no. 31 of 2004 concerning Fishery are amended, including the corporate criminal liability regulation. This research’s analyses shows that in order to improve the effectiveness of IUU Fishing law enforcement, specifically the ones being committed by a corporation, the Job Creation Law needs to be amended, specifically its article concerning corporate criminal liability, by changing the used conjunction to ‘and/or, as regulated in the draft of Fishery Law as well. Furthermore, as the term of ‘person in charge’ is more appropriate, in case of corporate criminal liability system, than the one used in the Job Creation Law, which is ‘employee’, the Job Creation Law shall be revised by opting the former term into it.